Cartesian Trajectory Tracking of a 7-DOF Exoskeleton Robot Based on Human Inverse Kinematics - Brahmi, Brahim; Saad, Maarouf; Rahman, Mohammad H.; Ochoa-Luna, Cristobal (IEEE transactions on systems, man, and cybernetics. Systems, 2019)
Exoskeleton robots have become an important tool to provide rehabilitation therapy to stroke victims because of their ability to allow rehabilitation exercises, ranging from passive to active-assisted movement, for extended time periods. To generate the desired rehabilitation trajectories and ensure an optimal Cartesian solution, we propose a new solution to the inverse kinematics problem, which is compatible with human upper limb movement and is valid for human arm configuration. In addition, in order to provide passive rehabilitation therapy to the upper extremity of disabled individuals, we implement a robust nonlinear control based on the backstepping technique on the 7-degrees-of-freedom ETS-MARSE robot. The controller was designed to reject the user's force caused by the subject's muscular activity. Experimental results validate the stability, robustness, and exactness of the proposed method with the designed tests performed by healthy subjects.